Use of fermented and non-fermented chicken bed in agricultural crop fertilization (Research, Society and Development, 2023)
Among the residues produced in poultry farming, the main by-product is chicken litter. The objective of the present work was to evaluate the use of fresh (non-fermented) and fermented chicken litter in the fertilization of corn and soybean seeds. The chicken litter collected and obtained in the third use in poultry sheds. A part of the compound was stored for 15 days and kept under refrigeration (CSF) and the part (CFF), was closed, stored at room temperature for 15 days. The experiments were carried out in the greenhouse of the IFMG – Campus Bambuí. Ten seeds of each cultivar were planted per pot, totaling 84 pots in DIC, divided into the three treatments and subsequently, the germination index, physical-chemical analyzes and quantification of ammonifying microorganisms were evaluated. There was an enrichment in the levels of macronutrients and micronutrients in the soils of the two treatments with residue compared to the control. However, the amount of ammonifying microorganisms in the soil reduced sharply in the treatment with CFF and the soil pH became more alkaline in the treatments with residues. The addition of poultry manure to the soil in the proportion used in the study (21ton/ha) caused germinative death of all seeds in the CSF and CFF treatments, making it impossible to analyze the germination test in these treatments. The work indicates that chicken litter, used in the experimental conditions of the study, is phytotoxic, therefore, its direct use in cultures at the tested concentration is not recommended, even fermented for 15 days.